Ganoderma boninense disease of oil palm to significantly reduce production after 2050 in Sumatra if projected climate change occurs - Paterson, R. Russell M. (MDPI, 2019)
Palm oil is a valuable crop. This relates to the high economic return from sales of the commodity, where Indonesia is the major producer in the world and the island of Sumatra is the most important region for palm oil production in the country. The island can be considered as a model for other oil palm growing regions in SE Asia. The area in Sumatra with a suitable climate for growing oil palm will decrease in size due to projected climate change as demonstrated specifically herein. The more unsuitable climate will lead to concomitant increases in basal stem rot (BSR) by Ganoderma boninense, as previously predicted, which is of major concern to sustainability in SE Asia. A novel approach is described herein, whereby (a) a determination of suitable climate for growing oil palm in Sumatra and (b) deductions to determine future BSR levels on the island were undertaken. The unsuitability of the climate for oil palm is predicted to increase dramatically after 2050 when BSR is predicted to increase to very high levels on most parts of the island. This is likely to make palm oil production unsustainable at some stage between 2050 and 2100. North Sumatra may be more sustainable than the other areas considered in Sumatra. These effects of projected climate change require amelioration before the high levels of BSR and the unsuitable climate for oil palm are realized.